Initiation of Meiotic Development Is Controlled by Three Post-transcriptional Pathways in Caenorhabditis elegans. Issue 4 (25th June 2018) - Mohammad, Ariz; Vanden Broek, Kara; Wang, Christopher; Daryabeigi, Anahita; Jantsch, Verena; Hansen, Dave; Schedl, Tim
Abstract: A major transition in germ cell development is the switch from mitotic cell cycling to entry into the meiotic developmental pathway. Mohammad et al. report that the SCF PROM-1 substrate-specific E3 ubiquitin ligase complex is a new... A major event in germline development is the transition from stem/progenitor cells to entry into meiosis and gametogenesis. This transition requires downregulation of mitotic cell cycle activity and upregulation of processes associated with meiosis. We identify the Caenorhabditis elegans SCF PROM-1 E3 ubiquitin-ligase complex as functioning to downregulate mitotic cell cycle protein levels including cyclin E, WAPL-1, and KNL-2 at meiotic entry and, independently, promoting homologous chromosome pairing as a positive regulator of the CHK-2 kinase. SCF PROM-1 is thus a novel regulator of meiotic entry, coordinating downregulation of mitotic cell cycle proteins and promoting homolog pairing. We further show that SCF PROM-1 functions redundantly, in parallel to the previously described GLD-1 and GLD-2 meiotic entry pathways, downstream of and inhibited by GLP-1 Notch signaling, which specifies the stem cell fate. Accordingly, C. elegans employs three post-transcriptional pathways, SCF PROM-1 -mediated protein degradation, GLD-1-mediated translational repression, and GLD-2-mediated translational activation, to control and coordinate the initiation of meiotic development.